Respostas

  • Usuário do Brainly
2013-03-10T20:19:36-03:00

d_{p,q}=\sqrt{(x_{p}-x_{q})^{2} + (y_{p}-y_{q})^{2}}

 

d_{p,q}=\sqrt{41}\\x_{p}=-2\\ x_{q}=2\\ y_{p}=m\\ y_{q}=3

 

Assim

\sqrt{(x_{p}-x_{q})^{2} + (y_{p}-y_{q})^{2}}=\sqrt{41}

 

\sqrt{((-2)-2)^{2} + (m-3)^{2}}=\sqrt{41}

 

\sqrt{(-4)^{2} + (m-3)^{2}}=\sqrt{41}

 

\sqrt{16 + (m-3)^{2}}=\sqrt{41}

 

16 + (m-3)² = 41

 

(m-3)² = 41 - 16

 

(m-3)² = 25

 

m-3 = +-25

 

m-3 = +25 => m = 25+3 => m = 28

m-3 = -25 => m = -25+3 => m = -22

 

P pode estar em dois pontos e a distância será a mesma